Innovative Approaches in Education: The Experience of Implementing the Credit-Modular System and Social-Emotional Learning - Rikhsiyeva, Umida (American Journal of Biomedicine and Pharmacy, 2025)
The credit-modular system has emerged as a modern pedagogical model that integrates modular teaching technologies with academic credits to increase flexibility, academic mobility, and international compatibility of higher education. This paper examines the theoretical and practical aspects of implementing the credit-modular system in Uzbekistan, analyzing its influence on the quality of professional training and exploring the integration of social-emotional learning (SEL). The study is based on a review of scientific literature, national policy documents, and practical experiences from higher education institutions in Uzbekistan and abroad. Results indicate that modularization improves flexibility and transparency, while credits ensure accurate measurement of workload and academic progress. Integrating SEL within the credit-modular framework develops competencies such as self-regulation, empathy, collaboration, and responsible decision-making, thus preparing well-rounded professionals. Findings suggest that the credit-modular system, combined with SEL, enhances both academic outcomes and personal growth, contributing to modernization and global alignment of higher education.